1994
DOI: 10.1007/bf01747905
|View full text |Cite
|
Sign up to set email alerts
|

Trace elements in the human environment: Problems and risks

Abstract: Early studies on the possible influences of environmental geochemistry and health were concerned with major diseases such as cancer or multiple sclerosis. They were generally confined to simple comparisons of geochemical and epidemiological maps and corresponding rural areas. Subsequently, studies of dental health produced evidence for the roles of environmental fluoride, selenium, molybdenum and lead in the aetiology of caries. In recent decades lead has been closely studied. Most people in the western world … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Experts have suggested that the dietary food program with high protein and high fat may increase the risk of MS ( 10 13 ). Apart from the mentioned risk factors, several studies have indicated that trace metals may have a role in the progression of neurodegenerative disorders ( 14 17 ). The aim of this study was to ascertain if the serum concentrations of Zn, Cu, Se, Mg and Pb are different between multiple sclerosis patients and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…Experts have suggested that the dietary food program with high protein and high fat may increase the risk of MS ( 10 13 ). Apart from the mentioned risk factors, several studies have indicated that trace metals may have a role in the progression of neurodegenerative disorders ( 14 17 ). The aim of this study was to ascertain if the serum concentrations of Zn, Cu, Se, Mg and Pb are different between multiple sclerosis patients and healthy controls.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high Pb level in the atmosphere can result in the high predicted level in the blood. Davies (1994) quoted the former Greater London Council which adopted a guideline Pb concentration of 0.5 mg/kg as justifying further investigation and 5 mg/kg as justifying control measures. The areal distribution of heavy metals with grain size suggests that the effects of grain size on the metal distribution in the aquifer system are not uniform throughout the basin.…”
Section: Ni V Cd Co and Pbmentioning
confidence: 98%
“…Lately, strong links have been noted between minerals in the soil and water, and the development of chronic degenerative conditions [3] [4] [5] [6]. Ions of trace and heavy metals such as iron, manganese, aluminum, mercury, lead, copper, chromium and cadmium have been linked to the initiation of numerous neurodegenerative disorders [1] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Existing research dictates that multiple interwoven factors, such as genetics, environment and diet influence an individual's health status and the expression of a disease state [3] [4] [5] [6]. Abnormalities at the genetic level have been proven to be largely influential in disorders of the brain like Parkinson's, Alzheimer's and Multiple Sclerosis [9] [10].…”
Section: Introductionmentioning
confidence: 99%